2011
DOI: 10.1073/pnas.1105682108
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of protein unfolding/refolding kinetics and structural characterization of hidden intermediates by NMR relaxation dispersion

Abstract: Detailed understanding of protein function and malfunction hinges on the ability to characterize transiently populated states and the transitions between them. Here, we use 15 N, 1 H N , and 13 CO NMR R 2 relaxation dispersion to investigate spontaneous unfolding and refolding events of native apomyoglobin. Above pH 5.0, dispersion is dominated by processes involving fluctuations of the F-helix region, which is invisible in NMR spectra. Measurements of R 2 dispersion for residues contacted by the F-helix regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 36 publications
5
113
0
Order By: Relevance
“…Ligands apparently bind only to the WT′-like state, displaying conformational selection in ligand binding and, at the same time, indicating that the new states excited by the cavity have alternative packing arrangements that apparently fill or partially fill the cavity, a suggestion that is in line with recent studies in other proteins containing native or engineered cavities (22,(30)(31)(32)(33). Precedent for this behavior in T4L is found in the extensively studied cavity mutant L99A, where it has recently been shown that a poorly populated (≈3%) conformational substate in equilibrium with the WT is one in which the cavity is partially filled with a native phenylalanine side chain (31).…”
Section: Discussionsupporting
confidence: 82%
“…Ligands apparently bind only to the WT′-like state, displaying conformational selection in ligand binding and, at the same time, indicating that the new states excited by the cavity have alternative packing arrangements that apparently fill or partially fill the cavity, a suggestion that is in line with recent studies in other proteins containing native or engineered cavities (22,(30)(31)(32)(33). Precedent for this behavior in T4L is found in the extensively studied cavity mutant L99A, where it has recently been shown that a poorly populated (≈3%) conformational substate in equilibrium with the WT is one in which the cavity is partially filled with a native phenylalanine side chain (31).…”
Section: Discussionsupporting
confidence: 82%
“…Expansions to three-state models require data of outstanding quality (Sugase et al 2007) and complexity, such as results from experiments conducted at multiple static magnetic field strengths or temperatures. In very favorable cases a three state model can be used without additional constraints such as addition of ligands or change of temperature (Meinhold & Wright, 2011). There exist a few cases in which three-state models have successfully been applied to proteins undergoing exchange, such as the study by Grey et al (2003) on the multiple states induced by disulfide bond isomerization in the basic pancreatic trypsin inhibitor, and the calculation of structural ensembles of folding intermediates for two Fyn SH3 domain variants reported by Korzhnev et al (2004).…”
Section: Exchange Modelsmentioning
confidence: 99%
“…Moreover, heteronuclear NOE data reveal gradients of fast backbone fluctuations in these helices not observed in native apoMb (42). Relaxation dispersion NMR showed the MG to be in pH-dependent equilibrium with other partially folded forms, indicating that the MG state also will be present in an equilibrium mixture at neutral pH, although with a small population relative to the native structure (i.e., an excited state) (39). Furthermore, this equilibrium MG was found to be structurally similar to the second of two intermediates identified during kinetic refolding by ultrafast hydrogen/deuterium (H/D) exchange coupled with 2D NMR (43).…”
mentioning
confidence: 99%
“…MGs typically are stabilized at low pH or in the presence of denaturants and are believed to represent intermediates in protein folding (38,39) and, in some cases, may mediate protein function (40). The MG of apomyoglobin (apoMb) stabilized at pH 4.1 is an ideal subject for exploring the structure and dynamics of such states because it can be populated under conditions suitable for study by high-resolution NMR (41).…”
mentioning
confidence: 99%